2017
DOI: 10.1017/s095457941700102x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health difficulties and academic attainment: Evidence for gender-specific developmental cascades in middle childhood

Abstract: We present a developmental cascade model of the longitudinal relationships between internalizing symptoms, externalizing problems, and academic performance in middle childhood, utilizing a large sample (N = 1,771) from the United Kingdom in a 3-year, cross-lag design. Three hypotheses were tested: adjustment erosion, academic incompetence, and (cumulative) shared risk. In addition, we sought to examine whether developmental cascade pathways varied across gender, while also statistically exploring indirect, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 74 publications
4
56
1
2
Order By: Relevance
“…We drew on a large, nationally representative data set that afforded important analytical advancements relative to much prior developmental cascade research (e.g., the estimation of latent variables, while also accounting for nesting in the data), thereby enhancing analytical rigour, while focusing separately on middle childhood and adolescence and examining potential differences between boys and girls. In contrast with Panayiotou and Humphrey (), multigroup analysis did not find evidence for gender differences for either age group.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…We drew on a large, nationally representative data set that afforded important analytical advancements relative to much prior developmental cascade research (e.g., the estimation of latent variables, while also accounting for nesting in the data), thereby enhancing analytical rigour, while focusing separately on middle childhood and adolescence and examining potential differences between boys and girls. In contrast with Panayiotou and Humphrey (), multigroup analysis did not find evidence for gender differences for either age group.…”
Section: Discussioncontrasting
confidence: 90%
“…Specifically, for primary school children, academic attainment was inversely related to later internalizing symptoms, even after accounting for shared‐risk variables; however, the same pathway was not present for adolescents. This finding is consistent with previous evidence of the effect of low academic competence on later internalizing symptoms specifically in middle childhood (Moilanen et al ., ; Panayiotou & Humphrey, ), which has highlighted the potential deleterious effects of academic failure on mental health (McCarty et al ., ). Explanations for the effect being observed for this specific age group include the potential impact of parent and teacher feedback around poor attainment on mood and self‐concept, especially leading up to transition from primary to secondary school settings (Moilanen et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the relationship between emotional health and educational attainment, [15][16][17][18] tests of interaction were also carried out to assess whether or not the effect of the intervention on the assessment of pupil progress (APP) outcomes is modified by whether or not the child scored in the struggling range on the teacher-reported SDQ-TD score at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…14 Promoting resilience at an early stage in life could lead to a population-level reduction in the burden and cost associated with mental ill health. In addition, poor mental health is highly associated with lower levels of academic attainment, [15][16][17] and recent work has demonstrated that improving a child's mental health will lead to subsequent improvements in their levels of attainment. 18 Therefore, an effective intervention that can be applied and delivered in an ordinary school setting, with no cost other than to train the teachers delivering it, would incur minimal costs for a wide-reaching population health benefit.…”
Section: Disruption In Schoolmentioning
confidence: 99%